Narasi Kepemimpinan Nani Wartabone Dalam Perjuangan Kemerdekaan Indonesia Di Gorontalo untuk Penguatan Karakter Siswa SMA - Ferrari Yuliawati Samsudin (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Gorontalo is one of the provinces located on the island of Sulawesi, at that time Gorontalo was still part of North Sulawesi but they decided to separate and create a new province. This paper describes how a son of Gorontalo was able to show his sense of nationalism and leadership towards the struggle for Indonesian independence, especially in pre-independence times in Gorontalo. Nani Wartabone is now a national hero. Nani Wartabone is the son of Gorontalo who began actively fighting for Indonesia since junior high school and he also worked a lot of leadership in the field of politics, social, education and economy. The method used in this writing is the study of literature from journals and books relevant to this article. The purpose of this literature review is to explore further the leadership of Nani Wartabone. From the results of this literature study can be drawn conclusions where the leadership attitude of Nani Wartabone can be used as a suri tauladan for high school students as a booster of leadership character in the future.